2019
DOI: 10.1002/ange.201903325
|View full text |Cite
|
Sign up to set email alerts
|

Silica‐Supported Molybdenum Oxo Alkylidenes: Bridging the Gap between Internal and Terminal Olefin Metathesis

Abstract: Grafting am olybdenum oxoa lkylidene on silica (partially dehydroxylated at 700 8 8C) affords the first example of awell-defined silica-supported Mo oxoalkylidene,whichisan analogue of the putative active sites in heterogeneous Mobased metathesis catalysts.Incontrast to its tungsten analogue, which shows poor activity towards terminal olefins because of the formation of as table off-cycle metallacyclobutane intermediate,t he Mo catalyst shows high metathesis activity for both terminal and internal olefins that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…It should be also noted that while we cannot identify the impurities mentioned, we have found that treatment of the olefin substrate with activated alumina and Selexsorb CD helps to remove them to a significant extent and considerably improves the performance of all the catalysts and the reproducibility of catalytic tests, [36] especially at low loading. [37] 1-Nonene. The supported catalysts were also tested in self-metathesis of 1-nonene as a prototypical terminal olefin.…”
Section: Catalytic Activitymentioning
confidence: 99%
“…It should be also noted that while we cannot identify the impurities mentioned, we have found that treatment of the olefin substrate with activated alumina and Selexsorb CD helps to remove them to a significant extent and considerably improves the performance of all the catalysts and the reproducibility of catalytic tests, [36] especially at low loading. [37] 1-Nonene. The supported catalysts were also tested in self-metathesis of 1-nonene as a prototypical terminal olefin.…”
Section: Catalytic Activitymentioning
confidence: 99%
“…Metathesis involving light alkenes is gaining importance as an atom economical route to augment the supply of certain olefinic feedstocks based on demand . Catalysts investigated widely for olefin metathesis include WO 3 , MoO 3 , and Re 2 O 7 supported on either SiO 2 or Al 2 O 3 . Because of its robustness towards poisons and relatively low cost, the WO 3 /SiO 2 catalyst has been widely used in industry to produce propene from ethylene and butenes.…”
Section: Introductionmentioning
confidence: 99%
“…SOMC, a molecular approach to generate well‐defined heterogeneous catalysts, in which the surface is exploited as a ligand to covalently anchor molecular complexes, has been particularly successfully employed for the preparation of silica‐supported Schrock‐type metathesis catalysts of the general formula [(≡SiO)M(E)(=CHR)(X)] (M=Mo or W, E=NR or O), that display high activity, selectivity and stability with performances often surpassing those of their homogeneous counterparts ( Scheme 1). [24–33] Yet, these metathesis catalysts display pronounced reactivity differences between terminal versus internal olefins, that depend on the metal and the σ‐donation ability of the X and E ligands. For example, increased activity in the metathesis of internal olefins is observed for weaker σ‐donating X‐ligands in supported metathesis catalysts bearing a donating imido ligand [26,28,31] .…”
Section: Introductionmentioning
confidence: 99%